PERAN BISNIS PARIWISATA DALAM INKLUSI KEUANGAN - Wahyu Fahrul Ridho (CV. Multi Kreasi Media, 2023)
The tourism business in Indonesia has a lot of potentials that could be utilized. This crucial sector of the economy could benefit society, especially the local community, in developing financial inclusion. However, the linkage between tourism and financial inclusion needs to be examined. This study gives perspective and examines the dynamic relationship between the tourism business and financial inclusion. This study is categorized as descriptive qualitative and utilizes a structured literature review by collecting literature data from a journal database. The main finding of this study is that the tourism business has a connection with financial inclusion through indirect effects. Financial inclusion indicators, which are economic welfare and availability and accessibility of financial services, were directly influenced by the tourism business and therefore impacted financial inclusion in the long run. This study does not examine the model constructed quantitatively, thus proposing future research to enhance the model by quantitative testing and examine additional variables such as socio-demographic conditions.